(untitled) (LEARNing Landscapes, 2010)
I am concerned about the hegemony of certain kinds of discourse in academic research. We need spaces for many kinds of research, including lifewriting research that focuses on narrative, autobiographical, fictional, and poetic knowing. Nevertheless, for all my enthusiasm for the value of lifewriting, I also recognize that lifewriting is fraught with dangers. There are many dangers in lifewriting, but there are also many dangers in avoiding lifewriting.Therefore, I promote poetry as a discursive practice that invites creative ways of writing a life in order to interrogate and understand lived and living experiences with more critical wisdom.